Between new and old poetry opinions and facts (Journal of the College of Basic Education, 2022)
The free poetry movement is a proven fact that has existed over generations, and it did not fail and did not extinguish its reputation because those who fought in it were writers from the first generation who had a stake in criticism and poetry and had their sound opinions. And that what came to us from free poetry while we were in the advanced years of the two thousandth, despite the progress and creativity of Tafilah poetry, I say that what reached us is an extension of the ideas of these early pioneers who entered into long battles and discussions in order to establish the outlines of another poetry that made its way in the face of bitter challenges. And if extraneous and tendentious parties try to obstruct the course of the movement and exclude it from the right, by creating unrest among poets, trying to mislead the facts by giving wrong opinions, an example of this is the American Poetry Magazine and the role of Ghali Shukri by issuing false opinions aimed at manipulating the terminology. In vain, poetry contains errors and omissions that do not limit in order to discredit the new poetry and make it a cause for ridicule.